Pengaruh Bauran Pemasaran dan Kualitas Pelayanan terhadap Keputusan Pembelian Konsumen - Muhamad Alfin Kuncoro; Muhamad Naely Azhad; Ahmad Izzudin (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the significant effect of product quality, price, location, promotion, and service quality variables on purchasing decisions at Warung Lesehan AA Jember. This research method is descriptive quantitative. The data processing technique uses multiple linear analysis tools. The results of this study indicate that the calculated t value obtained in multiple linear regression with product quality variable (X1) with a t count of 2.179 and a significance level of 0.031. Price variable (X2) with t count of 3.186 and a significance level of 0.002. Location variable (X3) with t count of 2.045 and a significance level of 0.043. Promotion variable (X4) with t count of 4.203 and a significance level of 0.000. Service quality variable (X5) with t count of 3.396 and a significance level of 0.001. And product quality, price, location, promotion and service quality have a simultaneous effect with F count of 30,014 with a significance level of 0,000. Product quality, price, location, promotion, and service quality affect purchasing decisions at Warung Lesehan AA Jember. Keywords: Product Quality, Price, Location, Promotion, Service Quality, and Purchase Decision